"We provide the methods to others but we don't use the methods ourselves": challenges with utilization of modern contraception among Female Healthcare Workers at two tertiary teaching hospitals, Northern Uganda - Jimmyy Opee; Keneth Opiro; Priscilla Manano; Margret Sikoti; Jackline Ayikoru; Harriet Akello; Fiona Gladys Laker; Maria K. Wolters; Silvia Awor; Francis Pebalo Pebolo; Felix Bongomin (BMC, 2024)
Abstract Background Female Healthcare Workers (FHCWs) play a crucial role in advocating for, delivering modern contraceptive methods (MCM) to reproductive-age women and potential users. Despite the high frequency of women seeking healthcare annually, less than half receive adequate contraceptive counseling and services. Investigating FHCWs' adherence to these practices and understanding the obstacles they encounter is essential. This study aimed to explore challenges with utilization of MCM among FHCWs at the two tertiary teaching hospitals in Northern Uganda. Methods We conducted a descriptive, cross-sectional study employing a qualitative approach at St. Mary's Hospital Lacor (SMHL) and Gulu Regional Referral Hospital (GRRH), Northern Uganda. Qualitative data were explored using the principles of descriptive phenomenology to gain deeper insights into the experiences of twenty (20) FHCWs. Results Findings revealed various challenges faced by FHCWs, including patient barriers such as religious beliefs, contraceptive myths, fear of side effects, and provider barriers like lack of knowledge, training, and discomfort. Additionally, health system barriers like limited time and competing priorities were identified. Conclusion Female Healthcare workers experience challenges with utilization of MCM. Efforts should focus on enhancing contraceptive services, particularly in faith-based facilities and among married individuals. Besides, addressing perceived barriers at the patient, provider, and system levels through comprehensive health education, ensuring method availability, and provider training is imperative.